Realizing Sustainable Growth: Innovative Talent Management Strategies in Driving Small and Medium-sized Enterprises Growth in the Creative Sector - Lewaherilla, Novalien Carolina; Almaududi Ausat, Abu Muna; Azzaakiyyah, Hizbul Khootimah; Rijal, Syamsu (CV Firmos, 2024)
The creative sector has emerged as a significant contributor to the global economy, including job creation and income generation. Despite its vast potential, SMEs in the creative sector often face challenges in achieving sustainable growth. This research aims to examine innovative talent management strategies in driving SME business growth in the creative sector to realize sustainable growth. The research method employed in this study is a literature review using a qualitative approach and descriptive analysis. Data for this research were gathered from Google Scholar for the period 2019-2024. The study findings indicate that in the face of globalization and rapid changes, the creative sector plays a crucial role in driving sustainable economic growth. SMEs play a vital role in the creative ecosystem, but they encounter various challenges, ranging from intense competition to limited access to resources. Innovative talent management is key to addressing these challenges and capitalizing on opportunities amidst evolving market dynamics. SMEs need to provide training and skill development for employees to strengthen their innovative capabilities.